The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1017/s1743921317006627
|View full text |Cite
|
Sign up to set email alerts
|

The age-metallicity structure of the Milky Way disc with APOGEE

Abstract: The best way to trace back the history of star formation and mass assembly of the Milky Way disc is by combining chemical compositions, ages and phase-space information for a large number of disc stars. With the advent of large surveys of the stellar populations of the Galaxy, such data have become available and can be used to pose constraints on sophisticated models of galaxy formation. We use SDSS-III/APOGEE data to derive the first detailed 3D map of stellar density in the Galactic disc as a function of age… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Figure1shows the distribution of each substructure in the Mg-Fe plane (coloured markers) compared to the parent sample (2D density histogram). We find that all the substructures -except for Aleph and Nyx-occupy a locus in this plane which is typical of low mass satellite galaxies and accreted populations of the Milky Way(Tolstoy et al 2009, Hayes et al 2018, Mackereth et al 2019, characterised by low metallicity and lower [Mg/Fe] at fixed [Fe/H] than in situ disc populations. For further details on these results, see Section 4.1 fromHorta et al 2022. …”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Figure1shows the distribution of each substructure in the Mg-Fe plane (coloured markers) compared to the parent sample (2D density histogram). We find that all the substructures -except for Aleph and Nyx-occupy a locus in this plane which is typical of low mass satellite galaxies and accreted populations of the Milky Way(Tolstoy et al 2009, Hayes et al 2018, Mackereth et al 2019, characterised by low metallicity and lower [Mg/Fe] at fixed [Fe/H] than in situ disc populations. For further details on these results, see Section 4.1 fromHorta et al 2022. …”
mentioning
confidence: 52%
“…The core of the Sagittarius dSph system and its still forming tidal stream (Ibata et al 1994) have long served as an archetype for dwarf galaxy mergers in the Milky Way. Moreover, in the past few years, several phase-space substructures have been identified in the field of the Galactic stellar halo that are believed to be the debris of satellite accretion events, including the Gaia-Enceladus/Sausage (GE/S, Helmi et al 2018;Belokurov et al 2018;Haywood et al 2018;Mackereth et al 2019), Heracles (Horta et al 2022), Sequoia (Myeong et al 2019), Thamnos 1 and 2 (Koppelman et al 2020), Nyx (Necib et al 2020, LMS-1 (Yuan et al 2020), the substructures identified using the H3 survey: namely Aleph, Arjuna, and I'itoi (Naidu et al 2020). While the identification of these substructures 94 D. Horta, R. P. Schiavon & the APOGEE team is helping constrain our understanding of the mass assembly history of the Milky Way, their association with any particular accretion event still needs to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…This is because, due to the inside-out disk formation, a MAP displays a negative age gradient (except for the lowest [α/Fe] MAPs). Flaring in the oldest APOGEE red clump stars was subsequently confirmed by Mackereth et al (2017), who used the same data and methods as Bovy et al and ages estimated by Martig et al (2016). This example emphasizes the importance of good ages estimates for disentangling the structure and formation of the Milky Way.…”
Section: Minchevmentioning
confidence: 73%